Actin isoforms and neoplastic transformation - V. B. Dugina; G. S. Shagieva; N. V. Khromova; P. B. Kopnin (Успехи молекулярной онкологии)
The cytoplasmic actins (β and γ) play crucial roles during key cellular processes like adhesion, migration, polarization and cytokinesis. The understanding of their specific underlying mechanisms would be of major relevance not only for fundamental research but also for clinical applications, since modulations of actin isoforms are directly or indirectly correlated with severe pathologies. The major goal of the research was to elucidate the function of the actin isoforms during motile activities, adhesions and cell division and to investigate whether their expression and/or structural organization is related to pathological function. Selective depletion of β- and γ-cytoplasmic actins allowed attributing functional diversities of β- and γ-сytoplasmic actins. β-Сytoplasmic actin plays a preferential role in contractile activities, whereas γ-cytoplasmic actin mainly participates in the formation of a submembranous network necessary for cell shape flexibility and motile activity. The roles of isoforms in regulating the integrity of adherens and tight junctions respectively were demonstrated. Unique roles of β- and γ-cytoplasmic actins in normal cells were shown. Similar results were obtained in cancer cells compared with normal epithelial cells in culture and in human pathological tissue sections of mammary gland, colon, lung and cervix. Malignant cell transformation requires changes in the ability of cells to migrate. The disruption of actin cytoskeleton and intercellular adhesions is an important component of the acquisition of invasive properties in epithelial malignancies.